1984
DOI: 10.1180/claymin.1984.019.4.04
|View full text |Cite
|
Sign up to set email alerts
|

Mode d'empilement des feuillets dans la vermiculite sodique hydratee a une couche (phase a 11·85 Å)

Abstract: RESUME: Comme la plupart des vermiculites, l'hydrate ~ une couche de la vermiculite-Na (d00 ~ = 11.85 /~) prbsente une structure semi-ordonn6e, avec des d6fauts d'empilement (glissements selon l'axe b). Le plan (hOl)* du r~seau r6ciproque est enti6rement discret, tandis que les rang~es n'appartenant pas ~t ce plan sont plus ou moins diffuses dans la direction c*. La projection xOz est obtenue par une classique analyse de Fourier bidimensionelle. Darts les plans (Okl)* et (lkl)*, certaines rang~es semblent pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 10 publications
3
18
1
Order By: Relevance
“…The quantitative agreement is very good between the two profiles and with previous studies based on X-ray diffraction analysis (Bradley et al 1963, Le Renard and Mamy 1971, de la Calle et al 1984.…”
Section: Interlayer Density Profilessupporting
confidence: 74%
See 3 more Smart Citations
“…The quantitative agreement is very good between the two profiles and with previous studies based on X-ray diffraction analysis (Bradley et al 1963, Le Renard and Mamy 1971, de la Calle et al 1984.…”
Section: Interlayer Density Profilessupporting
confidence: 74%
“…This result is expected from the trend observed for the montmorillonites, given the high tetrahedral layer charge in vermiculite. The appearance of a doublet, however seems to be in contradiction with the X-ray diffraction analyses of the monolayer hydrate of Na-vermiculite published by Bradley et al (1963), Le Renard andManny (1971), and de la Calle et al (1984), all of whom placed adsorbed Na + at the interlayer midplane. Skipper et al (1991 a) made the same inference in their neutron diffraction study of I 1.8 A Na-vermiculite.…”
Section: Interlayer Density Profilescontrasting
confidence: 44%
See 2 more Smart Citations
“…The study has confirmed the viability of the methods previously used by de la Calle et al (1984) to examine the one-layer Na-vermiculite structure. These methods relied upon the classical techniques of Fourier projections and also a method in which the observed intensities along each (0,k) and (1,k) reciprocal space rods were compared to the values of calculated intensities given by model defect structure (Plan~on, 1981;de la Calle et al, 1984). 4…”
Section: Introductionsupporting
confidence: 67%